3(y-6)=8y+22

Simple and best practice solution for 3(y-6)=8y+22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y-6)=8y+22 equation:


Simplifying
3(y + -6) = 8y + 22

Reorder the terms:
3(-6 + y) = 8y + 22
(-6 * 3 + y * 3) = 8y + 22
(-18 + 3y) = 8y + 22

Reorder the terms:
-18 + 3y = 22 + 8y

Solving
-18 + 3y = 22 + 8y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-8y' to each side of the equation.
-18 + 3y + -8y = 22 + 8y + -8y

Combine like terms: 3y + -8y = -5y
-18 + -5y = 22 + 8y + -8y

Combine like terms: 8y + -8y = 0
-18 + -5y = 22 + 0
-18 + -5y = 22

Add '18' to each side of the equation.
-18 + 18 + -5y = 22 + 18

Combine like terms: -18 + 18 = 0
0 + -5y = 22 + 18
-5y = 22 + 18

Combine like terms: 22 + 18 = 40
-5y = 40

Divide each side by '-5'.
y = -8

Simplifying
y = -8

See similar equations:

| P-3=11 | | 7+4=27 | | 6x+9=-4 | | N-3=-21 | | 2cosx=2-3sinx | | N-3=-23 | | -5w+3(w+5)=27 | | N^2+3n-128=0 | | K+12=1 | | 30-10x=-7(6-x) | | 7h+9=32 | | 19=a+1 | | 6p-6+40p=2+34p | | 6x+5-8x=-(2x-5) | | 1 = m3– 1 | | 7y-5-5y+2=0 | | 440x+25=230 | | Y=3x^2+17x+22 | | 25x+440=230 | | 2(x+4)-3=3(2x-3)+15 | | 30-10x=-7(x-6) | | 2x-6=59-11x | | 22-55+(85+65)=5 | | 25+3x=37 | | 6v-10=2v+2 | | 230x-25=440 | | 7x-7=x+29 | | 25x-230=440 | | c=38.51+0.50x | | 5x+2=-4(x-3) | | 6b+8a=9 | | 180=(20y-10)+2x |

Equations solver categories